Integration in the competency based undergraduate medical curriculum: A brief review - Rishabreddy D; Ayeesha Thajudeen (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: Integrated teaching in undergraduate medical curriculum aims to support meaningful learning to the students as it provides relevance to basic sciences in clinical practice, by matching learning with the way knowledge is to be used. This review aimed to highlight the pros and cons of integrated teaching in undergraduate medical curricula with proposed solutions. Materials & Methods: This was a brief review that was conducted by searching the database of PubMed with the keywords, Competency-based, Medical curriculum, Undergraduate, and Integration, from the year 2010 to 2022. Results: The search resulted in a total of 34 articles. Sixteen articles were excluded because the target audience was not medical. Thus a total of 18 articles are compared and tabulated. Most of the reviews and studies highlighted that integrated teaching reinforces and breaks the complexities of the students in understanding the practical knowledge required to develop a professional dedication to the care of the patients and make them lifelong learners. Major challenges discussed are duration, special training for facilitators, and preparing an elaborate module with specific learning objectives. Conclusion: The review highlights that integrated teaching has multiple benefits that are essential for a better understanding of the subjects and the academic performance of the students. However one must also acknowledge the existence of various challenges encountered at different levels of implementation and the proposed solutions that are addressed in this review.